Views of adolescents on addressing violence in semi-rural secondary schools in Mafikeng, North West province - Connie Mosome; Marie Poggenpoel; Chris Myburgh (AOSIS, 2011)
Background: Violence is a public health problem and often an issue of criminal justice.Violence in schools is a worldwide phenomenon and exposes adolescents to premature death. Purpose: The purpose of this study was to explore and describe adolescents' views on addressing violence in semi-rural secondary schools in Mafikeng. Research design and method: A qualitative, explorative, descriptive and contextual research design was utilised. Purposive sampling was used to select adolescents from semi-rural secondary schools in Mafikeng who fell between the ages of 13 and 20 years and who were involved in community youth groups or associations. In-depth focus group discussion using audiotape, reflexive notes and naïve sketches were used for data collection. The central question which was asked was 'What are the adolescents' views on addressing violence in semi-rural secondary schools?' Data were analysed by means of open coding. Results: The results showed that adolescents understood the complexities associated with violence in this country, and they suggested multiple approaches and interventions. The adolescents were of the opinion that responsible communication patterns in the school environment could build healthy relationships between learners and educators and lead to a decrease in violence in the school setting. They also felt that enforcement of a secure teaching environment through encouragement of behavioural and attitudinal change guided by school codes of conduct and provision of firm security will help reduce violence in schools.